Removal of phenol using sulphate radicals activated by natural zeolite-supported cobalt catalysts - Muhammad, Syaifullah; Saputra, E.; Sun, Hongqi; Ang, Ha-Ming; Tade, Moses; Wang, Shaobin (Springer Netherlands, 2013)
Two Co oxide catalysts supported on natural zeolites from Indonesia (INZ) and Australia (ANZ) were prepared and used to activate peroxymonosulphate for degradation of aqueous phenol. The two catalysts were characterized by several techniques such as X-ray diffraction, scanning electron microscopy, energy dispersive X-ray spectroscopy (EDS) and N2 adsorption. It was found that Co/INZ and Co/ANZ are effective in activation of peroxymonosulphate to produce sulphate radicals for phenol degradation. Co/INZ and Co/ANZ could remove phenol up to 100 and 70 %, respectively, at the conditions of 25 ppm phenol (500 mL), 0.2 g catalyst, 1 g oxone and 25 °C. Several parameters such as amount of catalyst loading, phenol concentration, oxidant concentration and temperature were found to be the key factors influencing phenol degradation. A pseudo first order would fit to phenol degradation kinetics, and the activation energies on Co/INZ and Co/ANZ were obtained as 52.4 and 61.3 kJ/mol,respectively.